Pengaruh Profesionalime Terhadap Kualitas Audit: Survey Pada Instansi Daerah Provinsi Jawa Barat - Boboy Adi Surya (Majalah Bisnis & IPTEK, 2022)
Researchers conducted research at the Inspectorate of West Java Province. This study aimed to determine and analyze the professional auditor, audit quality, and the magnitude of the influence of professionalism on audit quality in the inspectorate of West Java province. The research method used by the author is descriptive analysis and verification analysis, with 70 respondents. The results showed that the description of the professional auditor is in the good enough category, the audit quality is in the fairly good category. Furthermore, the correlation coefficient of 0.782 means that the relationship between professional auditors and audit quality is strong. At the same time, the regression is Y = 787.735 + 0.774, and the coefficient of determination of the influence of professional auditors on audit quality is 0.612 or 61.2%, while the remaining 38.8% influenced by other variables not examined, including skepticism, experience, and fraud.